2014
DOI: 10.1111/cas.12470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fibroblast growth factor receptor 2 attenuates proliferation and invasion of pancreatic cancer

Abstract: The alternative splicing of the extracellular domain of fibroblast growth factor receptor (FGFR)-2 generates the IIIb and IIIc isoforms. Expression of FGFR-2 IIIb correlates with vascular endothelial growth factor-A (VEGF-A) expression and venous invasion of pancreatic ductal adenocarcinoma (PDAC). By contrast, FGFR-2 IIIc expression correlates with faster development of liver metastasis after surgery, and increased proliferation rates and invasion of the cancer. In this study, we analyzed the expression and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
1
27
1
3
Order By: Relevance
“…Of note, a close spatial association was observed between proliferating tumour cells and microvessels, as determined using image analysis data in the present study; this therefore indicated an anatomical association between neovessel formation and tumour cell proliferation. In addition, this anatomical link may be supported by the overexpression of several angiogenic cytokines, including vascular endothelial growth factor, fibroblast growth factor, thymidine phosphorylase and tryptase, which have been previously demonstrated to be present in PDAC tissue (32)(33)(34)(35). These cytokines, secreted from tumoral and stromal cells, have a role in the autocrine and paracrine growth stimulation of tumoral and endothelial cells (36)(37)(38).…”
Section: Discussionmentioning
confidence: 93%
“…Of note, a close spatial association was observed between proliferating tumour cells and microvessels, as determined using image analysis data in the present study; this therefore indicated an anatomical association between neovessel formation and tumour cell proliferation. In addition, this anatomical link may be supported by the overexpression of several angiogenic cytokines, including vascular endothelial growth factor, fibroblast growth factor, thymidine phosphorylase and tryptase, which have been previously demonstrated to be present in PDAC tissue (32)(33)(34)(35). These cytokines, secreted from tumoral and stromal cells, have a role in the autocrine and paracrine growth stimulation of tumoral and endothelial cells (36)(37)(38).…”
Section: Discussionmentioning
confidence: 93%
“…In the colorectal cancer NCI-H716 cell line, which exhibits a high expression of FGFR2, the inhibition of FGFR2 by small molecule inhibitors or FGFR2 short hairpin (sh)RNA was shown to decrease cell viability (28). In pancreatic cancer, tumor cells with FGFR2-shRNA transfection exhibited attenuated proliferation rates, migration and invasion levels, and a reduced level of phosphorylation of ERK compared with that of the control cells (29). These findings demonstrate that the inhibition of FGFR2 contributes to the suppression of cell proliferation and ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Влияя на цис-регуляторные элементы, он активирует несколько генов [36], среди которых особенно важен ген IL-1. Секретируемый раковыми клетками IL-1 не влияет на сами эти клетки, но активирует близлежащие фибробласты, что приводит к повышению синтеза фибробластами FGF7, создавая таким образом положительную петлю обратной связи, усиливающую пролиферацию раковых клеток [37,38]. Одновременная экспрессия FGF7 и FGFR2-IIIb в тканях опухоли и стромы коррелирует с повышенной экспрессией VEGF-A (фактор роста сосудистого эндотелия А), венозной инвазией и негативным прогнозом.…”
Section: Fgfr2unclassified
“…Одновременная экспрессия FGF7 и FGFR2-IIIb в тканях опухоли и стромы коррелирует с повышенной экспрессией VEGF-A (фактор роста сосудистого эндотелия А), венозной инвазией и негативным прогнозом. FGFR2-IIIс потенцирует деление и миграцию клеток рака поджелудочной железы и придает им свойства, характерные для опухолевых стволовых клеток [21,37].…”
Section: Fgfr2unclassified